Layoff Tax and the Employment of the Elderly - Mario Schnalzenberger; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2008)
In 1996 Austria introduced a tax for the layoff of older workers, which was tightened in 2000. The regulation requires employers to pay a tax of up to 170 percent of the gross monthly income when they give notice to employees aged 50 or more. We use data from Austrian social security records to investigate if such layoff taxes lead to less firing of older workers. We compare a control group of workers aged nearly 50 with the treatment group above 50. We apply a difference-in-difference approach to analyze the difference in the displacement probability of all prime aged workers. Results show substantial reductions in layoff behavior for workers aged 50 and above after the tightening of the tax.
Keywords: J14; J45; J63; 330; Layoff tax; labor demand; employment; elderly workers; Kündigung; Ältere Arbeitskräfte; Steuerpolitik; Gesetzliche Rentenversicherung; Österreich